ANALISIS POTENSI PERTANIAN DAN PARAWISATA AIR PANAS TUTI SEBAGAI SEKTOR UNGGULAN DESA AIR MANCUR - Rani Puspa Atakama; Muhamad Songge; Noni Wulandewi Maulau; Pertus MauTelu Dony (Adiba Aisha Amira, 2026)
This study aims to analyze the potential of the agricultural sector and Tuti Hot Spring tourism as leading sectors that can support economic development in Air Mancur Village. Using a descriptive qualitative approach, data were collected through direct field observations, in-depth interviews with local residents and village authorities, and documentation reviews. The findings indicate that agriculture remains the primary livelihood source for the community, supported by key commodities such as maize, upland rice, coconuts, cassava, and various horticultural products that hold significant economic value for both local consumption and nearby markets. Meanwhile, Tuti Hot Spring represents a unique natural attraction characterized by its geothermal features, offering considerable potential to be developed into a prominent tourism destination. However, tourism development faces several challenges, including limited access infrastructure, inadequate supporting facilities, low promotion efforts, and insufficient community involvement in destination management. The study concludes that optimizing these two sectors requires an integrated strategy that includes capacity building for local communities, strengthening village institutions, improving basic infrastructure, and promoting tourism based on local potential and sustainability principles. With appropriate planning and implementation, the agricultural sector and Tuti Hot Spring tourism can become key drivers of sustainable village development.